Organizational study of an Urban Malay settlement: the case of Kampung Baru - Md Yassin, Khairil Azhar; Othman, Mohamed Aris (Postgraduate Student Society IIUM, 2007)
The objective of this study is twofold. First, it attempts to explore the organizational structure of an urban Malay settlement namely Kampung Baru, and second it tries to see the connection between the organizational structure and development process at Kampung Baru. This study employs qualitative research methodology, which relies heavily on the intensive interview with the officers from Kuala Lumpur City Hall [KLCH/DBKL] and Administration Board of Malay Agricultural Settlement of Kampung Baru [M.A.S]. Analysis of secondary data such as state government gazette, memorandum and government policies and plans is also utilized. From the data, it is found out that there is a kind of dual organizational structure exists in Kampung Baru and each structure enjoys its own areas of jurisdiction. However, from time to time there is a struggle between these two structures since their areas of jurisdiction are seems to be overlapping. This in the end, in one way or another hinders the development process in Kampung Baru.